Horner 증후군을 동반한 Ross 증후군 1예 - 최문정; Moon Jeong Choi; 최동규; Dong Gyu Choi; 김상윤; SanYun Kim (Daihan angwa haghoi jabji, 1998)
Ross증후군은 긴장동공, 건반사의 소실, 분절성 무한증의 증세를 보이는 말초신경계의 질환으로 교감신경, 부교감신경 및 dorsal root ganglion의 신경절 세포와 절후섬유의 이상으로 발생하게 된다. 저자들은 우측 안검하수와 안면무한증을 보이는 46세 여자에서 동공부등이 발견되어 starchiodine 발한검사를 포함한 신경학적 검사 및 각종 조건에 따른 동공의 변화를 관찰하고, Infrared Scanning Laser Photography(HRA , Heidelberg engineering, Germany)를 이용하여 동공 크기를 기록하였다. 이에 교감신경 및 부교감신경이 동시에 침범된 `Horner증후군을 동반한 Ross증후군`으로 진단되어 문헌고찰과 함께 보고하는 바이다(한안지 39:2201∼2205, 1998). Ross syndreome is a rare peripheral nervous system disorder defined by Adie` tonic pupil, hyporeflexia, and segmental anhidrosis. The pathogenesis is believed to result from damage to the ganglion cells or postganglionic fibers, including sympathetic, parasympathetic and dorsal root ganglion cells. A 46 year-old woman complained of right ptosis and decreased sweating of right face. The pupil showed anisocoria, which was evaluated under the variable conditions and recorded with the pupillography using Infrared Scanning Laser Photography(HRA , Heidelberg engineering, Germany). The neurologic examinations including starch-iodine test demonstrated areflexia of lower limbs and hypohidrosis of right face. The above examinations provided evidences that the sympathetic and parasympathetic ganglion cells or the post ganglionic fibers were involved and the diagnosis of Ross syndrome with Horner syndrome was made(J Korena Ophthalmol Soc 39:2201∼2205, 1998)